Implementasi Time-Driven Activity-Based Costing Berdasarkan Pelanggan untuk Meningkatkan Profitabilitas : (Studi Kasus Kantor Akuntan Publik XYZ) - Sugianto, Deby; Adang, Ferry (OGZ Research & Publishing, 2024)
Time-Driven Activity-Based Costing (TDABC) is considered essential for management decision-making, particularly in determining whether to retain or discontinue relationships with clients, in order to achieve sustainable profitability. The application of TDABC in accounting firms is expected to have a positive impact and provide relevant information for decisions aimed at improving profitability. This study aims to maximize profitability margins and cost efficiency in the audit and assurance services sector, focusing on KAP XYZ. The research method employed is qualitative, using descriptive analysis, with primary data collected through interviews and observations, and secondary data obtained from KAP. The results indicate that the implementation of TDABC requires a cost driver based on work hour allocation. Based on the analysis of customer profitability - cost to serve, one client was characterized as